The Role of the Family in Overcoming Stunting through the Probebaya Program in the Bukuan Kelurahan Area, Samarinda City - Adi, Nugroho; Eny, Rochaida; Budi, Suharto Rahcmad (KnE Social Sciences, 2024)
This study aims to determine the role of the local government in the digital and pandemic era in alleviating stunting in Indonesia. This type of research is qualitative. The research method uses in-depth interviews and triangulation for data analysis. Sources of data from key informants and informants from the office and the community in Bukuan Kelurahan Kota Samarinda. The results show that the Community Development and Empowerment program (PROBEBYA), implemented by the Local Government of Samarinda City, in Kalimantan, Indonesia, has been implemented in various regions through the infrastructure program (economy, social culture, and health). By running this program, the community is greatly assisted even though it is seen that the stunting rate is quite high, the government’s efforts experienced many obstacles in its implementation efforts because there are still many people who shut themselves down and are ashamed that their children are malnourished. And the ability of families to meet the nutritional needs of children is obtained from prepared food, served instantly. Keywords: information mobilization, program stunting, community welfare